Book Review: How to Do Things You Hate - Reframing Discipline, Motivation, and Discomfort - Jiang, Yuzhi (International Journal of Humanities and Social Science, 2025)
Peter Hollins's How to Do Things You Hate explores the psychological foundations of motivation, procrastination, and self-discipline through insights from cognitive and emotional science. Drawing on theories of emotion regulation, self-determination, and habit formation, Hollins reframes resistance to unpleasant tasks as an adaptive emotional mechanism rather than a personal shortcoming. The book argues that sustained action stems not from sheer willpower but from an understanding of how emotions, identity, and environmental factors interact to influence behavior. This review analyzes Hollins's integration of behavioral research with practical strategies, emphasizing his focus on emotional intelligence, cognitive reframing, and environmental design as effective tools for overcoming avoidance. It further assesses the book's strengths in clarity and theoretical coherence, while noting its occasional oversimplifications of neuroscience and sociocultural dynamics. Overall, How to Do Things You Hate presents a compassionate, evidence-based perspective on productivity that prioritizes psychological flexibility and self-awareness over rigid discipline.